2020
DOI: 10.1002/jimd.12292
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of adult patients with noncirrhotic hyperammonemia

Abstract: Adult-onset noncirrhotic hyperammonemia (NCH) is poorly understood and has a high morbidity and mortality. To elucidate the etiology and management of NCH, we performed a retrospective analysis of 23 adults (median age 51) with NCH treated between 2014 and 2020 at two academic medical centers. Hyperammonemia was diagnosed in all cases during the evaluation of altered mental status, with 22% presenting with seizures. Peak ammonia levels were >200 μmol/L in 70% of cases. Defects in ammonia metabolism were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…A flowchart shows the search process and study selection (Figure 1). We identified 18 relevant articles, which met the inclusion criteria for qualitative synthesis, of which 13 were case reports 13,23–34 and 2 were case series 16,35 . Only 3 were included for meta‐analysis 15,17,36 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A flowchart shows the search process and study selection (Figure 1). We identified 18 relevant articles, which met the inclusion criteria for qualitative synthesis, of which 13 were case reports 13,23–34 and 2 were case series 16,35 . Only 3 were included for meta‐analysis 15,17,36 …”
Section: Resultsmentioning
confidence: 99%
“…Three studies 29,31,34 reported using azithromycin, levofloxacin, and doxycycline to manage hyperammonemia syndrome in these patients. Based on 14 studies, 13,16,23–35 the median length of treatment for HS patients was 21 (range: 2–120) days. For those patients who were started on initial treatment with β‐lactam antibiotics ( n = 2), symptoms and ammonia levels of HS did not improve 23,28 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations